Analysis of double-frequency jitter on time-delayed oscillators networks and perturbations adjustment in clock - Felix, R. O. [UNESP]; Bueno, A. M. [UNESP]; Correa, D. P.F.; Balthazar, J. M. [UNESP] (Springer Nature, 2021)
The delay in signal transmission for oscillator networks influences in the synchronization, getting oscillatory behavior. The synchronization occurs by the phase-locked loops (PLL), synchronizing the local oscillator with a reference phase and frequency. The oscillators are implemented in data and telecommunications communication systems, as elements (nodes) for distribution of time signals (clock). In the work is implementated the time signal distribution network, with three nodes, in order to establish a common time base, with adjustment of disturbance in clock. The phase detection process generates a periodic oscillation called double-frequency jitter (DFJ). The DFJ is inevitable, appearing even with the PLL operating in the blocking range. Therefore, this work aims to study the effect of the double frequency oscillation on a network with signal transmission delay, its influence on the synchronous states of network, and the performance of oscillators to recover the common time base of clock, when disturbed.